INTERDISCIPLINARY INTEGRATION - THE BASIS OF PROFESSIONAL ORIENTATION TRAINING - Карпець, М.В. (World of Medicine and Biology, 2016)
The article shows the importance of medical chemistry course in forming medical student and future highly qualified specialists. The condition for the success of a holistic approach to teaching medical chemistry in higher medical education is interdisciplinary integration of the disciplines of medical and biological (biochemistry, physiology, bioorganic chemistry, pharmacology, medical and biological physics) and clinical profile (pathological physiology, clinical biochemistry, hygiene, toxicology, therapy, anesthesiology, physical therapy, resuscitation, etc.). This approach significantly increases the motivation to study.
Keywords: medicinal chemistry; interdisciplinary integration; interdisciplinary communication